The Electric Field Modulation by Hemisphere Damage Sites in Fused Silica Subsurface - Shaobo He; Liang Yang; Li Li; Xiao-Tao Zu (Advances in Condensed Matter Physics)
The effect of defect density on the electric field modulation to incident laser is investigated in this work. Based on the actual defect distribution in fused silica subsurface, the three-dimension grid model of defect sites is constructed firstly. Then, the three-dimension finite-difference time-domain method is developed to solve the Maxwell equations. The electric field intensity in the vicinity of the defect sites located in front subsurface of fused silica is numerically calculated. The relationships between the maximal electric field intensity in fused silica and the geometry of the defect sites are given. The simulated results reveal that the modulation becomes more remarkable with the increase of defects density firstly and then decrease. Besides, the effect of the distribution mode of defects on modulation is discussed. Meanwhile, the possible physical mechanism is analyzed in detail.